Reliability of common neuromuscular performance tests in adolescent athletes - Haines, B. R.; Bourdon, P. C.; Deakin, G. (Journal of Australian Strength and Conditioning, 2016)
The purpose of this study was to examine the reliability of four commonly used neuromuscular tests and their associated variables in adolescent athletes. A total of 17 male adolescent athletes (age 16.5 ± 1.1 years, height 171.2 ± 6.3 cm, body mass 65.5 ± 11.2 kg) performed a test battery consisting of the countermovement jump (CMJ), drop jump (DJ) , isometric mid-thigh pull (IMTP), all performed on a force plate and 20-m sprint on two consecutive days. Inter-day reliability of a number of variables from each test was determined using the coefficient of variation (CV) and intraclass correlation coefficient. A number of variables within each test were found to have acceptable inter-day reliability (CV < 10%) with corresponding reliable ICC values greater than 0.75. For the CMJ and DJ peak concentric impulse (CV = 1.6%; ICC = 0.99 and 5.1%; 0.94 respectively) and take-off velocity (CV = 1.7%; ICC = 0.97 and 4.8%; 0.85 respectively) were the most reliable variables. Other commonly reported variables also showed acceptable levels of reliability for both tests such as peak power (CV = 3.2%; ICC = 0.98 and 6.1%; 0.95) and jump height (CV = 3.4%; ICC = 0.96 and 9.8%; 0.85, respectively). Peak force was the most reliable variable in the IMTP (CV = 6.4%; ICC = 0.87) as was the 20-m split time for the 20-m sprint (CV = 0.8%; ICC = 0.98). Peak RFD was not found to be reliable in any of the tests it was measured (CMJ, DJ and IMTP). The results of this study indicate that the CMJ, DJ, IMTP, 20-m sprint are reliable measures of performance in adolescent athletes.